Governing the Contemporary Administrative State - Trondal, Jarle. author. aut Link
XVIII, 346 p. 15 illus.
Keywords: This book examines the transformation of the administrative state, since it was first coined by Dwight Waldo seventy years ago. Empirically, the book assesses how the administrative state is facing endogenous reforms through administrative devolution, as well as exogenous shifts by the rise of multilevel administrative systems and international bureaucracy. Facing dual shifts, the book offers a comprehensive analysis of how the administrative state handles three interconnected challenges: first, a need for innovation and reform as well as stability and robustness; second, administrative autonomy among regulatory bodies as well as political leadership and democratic accountability; and third, nation-state sovereignty as well as international collaboration. It also highlights the robust character of the administrative state by demonstrating profound stability in public governance even during times of profound turbulence. It will appeal to scholars and students of public policy, public administration and global governance, as well as practitioners interested in new developments in public governance. Jarle Trondal is Professor in the Department of Political Science and Management, University of Agder, Norway; Professor at ARENA Centre for European Studies, University of Oslo, Norway; and Senior Fellow at The Institute of European Studies, University of California, Berkeley, US. His research interests include European public administration, administrative behavior and reform, global governance, and organizational studies.